Laser scribed proton exchange membranes for enhanced fuel cell performance and stability - Jianuo Chen; Xuekun Lu; Lingtao Wang; Wenjia Du; Hengyi Guo; Max Rimmer; Heng Zhai; Yuhan Liu; Paul R. Shearing; Sarah J. Haigh; Stuart M. Holmes; Thomas S. Miller (Nature Communications)
Abstract High-temperature proton exchange membrane fuel cells (HT-PEMFCs) offer solutions to challenges intrinsic to low-temperature PEMFCs, such as complex water management, fuel inflexibility, and thermal integration. However, they are hindered by phosphoric acid (PA) leaching and catalyst migration, which destabilize the critical three-phase interface within the membrane electrode assembly (MEA). This study presents an innovative approach to enhance HT-PEMFC performance through membrane modification using picosecond laser scribing, which optimises the three-phase interface by forming a graphene-like structure that mitigates PA leaching. Our results demonstrate that laser-induced modification of PA-doped membranes, particularly on the cathode side, significantly enhances the performance and durability of HT-PEMFCs, achieving a peak power density of 817.2 mW cm⁻² after accelerated stress testing, representing a notable 58.2% increase compared to untreated membranes. Furthermore, a comprehensive three-dimensional multi-physics model, based on X-ray micro-computed tomography data, was employed to visualise and quantify the impact of this laser treatment on the dynamic electrochemical processes within the MEA. Hence, this work provides both a scalable methodology to stabilise an important future membrane technology, and a clear mechanistic understanding of how this targeted laser modification acts to optimise the three-phase interface of HT-PEMFCs, which can have impact across a wide array of applications.